Implementation of opportunistic salpingectomy for ovarian cancer prevention: Analyzing clinical practice and key characteristics - Charlotte Fisch; Malou E. Gelderblom; Brigitte Slangen; Angèle L. M. Oei; Alexandra A. vanGinkel; Huy Ngo; Joanne deHullu; Jurgen Piek; Rosella Hermens (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Ovarian cancer (OC) is the most lethal gynecologic cancer, often diagnosed at an advanced stage due to nonspecific symptoms and lack of effective screening. Over 90% of all ovarian cancer cases are epithelial in origin, which is thought to originate from the fallopian tubes in approximately 70% of cases. Opportunistic salpingectomy (OS), the additional removal of fallopian tubes during abdominal surgery, has emerged as a preventive strategy. Despite growing evidence, the implementation of OS varies widely. This study examines OS counseling and performance trends in the Netherlands from 2019 to 2022 and identifies associated patient, surgical, physician, and institutional characteristics. Material and Methods A historical cohort study was performed, analyzing electronic medical records from six Dutch hospitals, including two academic, two teaching, and two nonteaching hospitals. Patients undergoing elective gynecologic surgery from January 2019 to December 2022 were considered eligible. Multilevel logistic regression analyses identified characteristics associated with counseling and performance of OS. Results Out of 2716 eligible patients, 51% were counseled about OS, of whom 92% opted for the procedure. The counseling rate increased from 38% in 2019 to 57% in 2022, while the performance rate rose from 39% to 56%. OS was more common among patients undergoing hysterectomy, laparoscopic surgery, and treatment at teaching hospitals. OS was less common during vaginal surgery. Physician characteristics accounted for 18% of counseling and 12% of performance variations. Conclusions Although OS implementation improved, substantial variability remains in counseling and performance, largely driven by surgical approach and type of surgery. Targeted interventions to enhance uptake among underutilized surgical types, including vaginal procedures, are necessary to standardize OS practice and ensure wider adoption across all eligible patients.